Análise política da disciplina de cultura digital, do novo Ensino Médio - Testa, Mauricio José (2024)
The research developed in this dissertation is centered on investigating the new curricular discipline entitled Digital Culture (CD), through three studies. In order to have an idea of how the National Common Curricular Base (BNCC) incorporated the CD discipline, in the introduction, we reflect on the implementation of the New Secondary Education, through the BNCC, carrying out a structured critique of the document. Continuing, in the first study, an investigation is carried out in the publications of national journals with the best evaluation in Qualis CAPES in the broad area of Teaching, focusing on publications in the sub-areas of Physics Teaching and Science Education. The second study seeks to understand the way in which the Schools of the 16th Regional Education Coordination in the Serra Gaúcha region are working with the CD discipline and finally, the third study, seeks to integrate the disciplines of Natural Sciences and their Technologies (CNT) with that of CD. In the first article, we noted the importance of implementing the CD discipline in all teaching modalities, enhancing the construction of knowledge through the help of technologies. In the second, we showed that teachers are not able to develop the CD discipline, pointing out the lack of specific materials and initial and continuing training. Finally, in the third article, we present a didactic proposition as an alternative to the scarcity of Training Itineraries linked to Natural Sciences, being explored through the use of Digital Information and Communication Technologies (TDIC) and Artificial Intelligence (AI).